Effect of inhaled corticosteroids on blood eosinophil count in steroid-naïve patients with COPD. Issue 1 (8th September 2016) - Kreindler, James L; Watkins, Michael L; Lettis, Sally; Tal-Singer, Ruth; Locantore, Nicholas
Abstract : Introduction: Sputum and blood eosinophil counts have attracted attention as potential biomarkers in chronic obstructive pulmonary disease (COPD). One question regarding the use of blood eosinophils as a biomarker in COPD is whether their levels are affected by the use of inhaled corticosteroids (ICS), which are commonly prescribed for COPD. Methods: We performed a retrospective analysis of peripheral blood leucocytes from a previously completed clinical trial that examined effects of ICS in steroid-naïve patients with COPD. Results and conclusion: The data show that the ICS-containing treatment arms (containing fluticasone propionate) had a small effect on peripheral blood eosinophils in steroid-naïve patients with COPD. Trial registration number: NCT00358358; Post-results.